Interventions to reduce verocytotoxigenic Escherichia coli in ground beef in Argentina: A simulation study - Signorini Porchietto, Marcelo Lisandro (2010)
A stochastic simulation model was used to assess the effects of measures implemented in the agri-food-chain to reduce the contamination of ground beef with verotoxigenic Escherichia coli (VTEC). A published risk assessment model developed in Argentina was used as baseline scenario. Control measures assessed were based on either a reduction in herd prevalence of infection due to vaccination, reduction in opportunity for cross-contamination in the slaughterhouses by the introduction of an on-line hide-wash cabinet, and control of storage temperature in slaughterhouses, retail and home. Additionally, the increase of feedlot production was modelled. Simulations suggested that the greatest potential impact was associated with hide-wash cabinet and vaccination, measures aimed to reduce the VTEC prevalence and concentration in the cattle hides at the beginning of the food-chain. Control of storage temperature was not effective if the carcasses cross-contamination with the pathogen was not prevented or reduced. An increase production (fattening) of cattle in feedlots may raise the risk of VTEC infection and its sequelae. This information can be used as a basis for measures of risk management.